2020
DOI: 10.1002/ejp.1691
|View full text |Cite
|
Sign up to set email alerts
|

Faces of clinical pain: Inter‐individual facial activity patterns in shoulder pain patients

Abstract: Background Facial activity during pain is composed of varying combinations of a few elementary facial responses (so‐called Action Units). A previous study of experimental pain showed that these varying combinations can be clustered into distinct facial activity patterns of pain. In the present study, we examined whether comparable facial activity patterns can also be identified among people suffering from clinical pain; namely, shoulder pain. Methods Facial expressions of patients suffering from shoulder pain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“… 16 It is important to realize that these facial movements are not typically displayed together when somebody is in pain, as individuals usually show different mixtures of each facial movement. 17 , 18 The most frequent response to pain is a tightening of the muscles around the eyes, paired with one or two other pain-indicative facial movements.…”
Section: Changes In Pain Expression In Dementiamentioning
confidence: 99%
“… 16 It is important to realize that these facial movements are not typically displayed together when somebody is in pain, as individuals usually show different mixtures of each facial movement. 17 , 18 The most frequent response to pain is a tightening of the muscles around the eyes, paired with one or two other pain-indicative facial movements.…”
Section: Changes In Pain Expression In Dementiamentioning
confidence: 99%
“…The models and solutions that have shown promise for automatic detection are based on limited sampling. There is considerable evidence from direct facial measurement studies that facial expressions of pain involve a common core of actions (23,52), but recent findings indicate that those actions come in different clusters (73,74). This points to a need to collect further databases that sample a broader range of pain types as a way to assess the generality and generalizability of extant and novel models and solutions.…”
Section: Generalizabilitymentioning
confidence: 99%
“…Kunz et al recently reported that among participants with shoulder pain undergoing passive movement of the joint, the most common cluster of facial expression was “narrowed eyes” related to contracture of AU6/7. The facial activity was displayed in approximately 40% of participants on repeated exposure to movement of their shoulder ( 19 ). The authors also reported another cluster of facial activity, which involved AU6/7, AU4 (brow lowering), and AU43 (eye closure) in approximately 10% of participants (“narrowed eyes with furrowed brow and closed eyes”) ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…The facial activity was displayed in approximately 40% of participants on repeated exposure to movement of their shoulder ( 19 ). The authors also reported another cluster of facial activity, which involved AU6/7, AU4 (brow lowering), and AU43 (eye closure) in approximately 10% of participants (“narrowed eyes with furrowed brow and closed eyes”) ( 19 ). This is in line with our findings that suggest that the upper face (i.e., eyes and forehead) appears to be the most expressive region of the face in moderate-severe pain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation